Predictors of glucose metabolism and blood pressure among Ethiopian individuals with HIV/AIDS after one‐year of antiretroviral therapy. Issue 4 (2nd February 2021) - Amare, Hiwot; Olsen, Mette F.; Friis, Henrik; Andersen, Åse B.; Abdissa, Alemseged; Yilma, Daniel; Girma, Tsinuel; Faurholt‐Jepsen, Daniel
Abstract: Objective: Better understanding of glucose metabolism in patients with HIV after initiating antiretroviral therapy (ART) is important to target treatment and follow‐up for diabetes risk and other non‐communicable diseases in resource‐limited settings. The aim of this study was to assess the changes and predictors of glucose metabolism and blood pressure among patients with HIV on ART for 12 months. Methods: One‐year follow‐up of Ethiopian patients with HIV after initiation of ART was done. Outcomes were changes in fasting plasma glucose (FPG), and 30‐minute (30mPG) and 2‐hour plasma glucose (2hPG) after oral glucose tolerance test, glycated haemoglobin (HbA1c), fasting plasma insulin (p‐insulin), homeostatic model assessment index for insulin resistance (HOMA‐IR) and blood pressure.   Results: The mean age was 33 years, and the majority were women. During the first 12 months, levels of all plasma glucose parameters decreased, while p‐insulin (10 B 3.1; 95% CI2.4, 4.0), HOMA‐IR (10 B 3.1; 95% CI2.3, 4.0) and systolic blood pressure (B 4.0; 95% CI2.5, 5.5) increased. Fat‐free mass at baseline predicted higher increments in p‐insulin, HOMA‐IR and blood pressure; whereas, fat mass predicted higher increment in HbA1c. Conclusions: Among Ethiopian patients with HIV, blood pressure and insulin increased, and all glucose parameters declined during 12‐month of ART. Only longer‐term follow‐up will tell us whether insulin increase is due to insulin resistance or from recovering β‐cells.